A rare case of superior ophthalmic vein thrombosis and thrombocytopenia following ChAdOx1 nCoV-19 vaccine against SARS-CoV-2 - Irina Panovska-Stavridis (Mediterranean Journal of Hematology and Infectious Diseases)
x